Abiotic stress caused by foliar applications of boron to the yellow diploid potato (Solanum tuberosum, Group Phureja) cultivar Criolla Galeras - Gómez, Manuel Iván; Restrepo, Hermann; Rodríguez, Luis Ernesto; Magnitskiy, Stanislav; Manrique, Lady; Garzón, Alfonso (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Foliar applications of boron (B) constitute a frequent practice in the fertilization of the yellow diploid potato and are generally done with excessive and empirical doses generating toxicities in crops. The effect of foliar applications of B at doses of 0, 0.5, 1.2, or 4 kg ha-1 was determined for physiological and metabolic variables and toxicity symptoms in the yellow diploid potato cultivar Criolla Galeras under greenhouse conditions using Na octaborate (20.5% B, 11% Na) or boric acid (17.5% B) as sources of B. Significant differences (P<0.05) were found between the sources and doses for dry matter (DW), leaf area (LA), proline content, and electrolyte leakage (ECh). The highest toxicity was observed for B applied as sodium octaborate at concentrations of 2 and 4 kg ha-1 B with a reduction of DM up to 40%, a decrease of LA up to 90%, a loss of 60% in ECh, and a significant increase in the concentration of proline (65 μmol/g fresh weight). The lower toxicity of boric acid at doses higher than 2 kg ha-1 B indicated that the octaborate Na presented synergism with B, which can result in a greater oxidative stress, causing instability of the membranes, necrosis and premature tissue death, as evidenced in the description of the visual symptoms. The doses of 0.5 and 1.0 kg ha-1 B for both sources resulted in positive responses in the DW and non-significant (P<0.05) differences with the control, associated with the levels of proline and ECh, which indicated a narrow range between the deficiency and toxicity of B for cv. Criolla Galeras, where the effect of the accompanying ion must be considered in the selection of the boron source.